(untitled) (Lentera Masyarakat Hukum, 2025)
Introduction: In Indonesia’s rapidly urbanizing areas, many low-income individuals and families struggle to access social services due to bureaucratic barriers, legal illiteracy, and financial constraints. Legal aid clinics play a critical role in addressing these issues by offering free or affordable legal services to vulnerable populations. Purpose: This paper examines the role of legal aid clinics in addressing social welfare issues, focusing on how they contribute to improving access to social services such as healthcare, housing, and social security. Method: The study uses a case study approach to explore several legal aid clinics in urban areas of Indonesia, conducting interviews with staff, beneficiaries, and social welfare experts. The study also examines case outcomes to assess the effectiveness of these services in improving access to social support. Findings and Results: The research finds that legal aid clinics provide essential assistance in helping low-income individuals navigate legal complexities related to social welfare. However, the study also identifies gaps in coverage, such as insufficient outreach to remote areas and a lack of capacity to handle increasing demand. Urgency: Given the growing numbers of urban poor and the rising demand for social welfare services, expanding and improving legal aid services is an urgent need to prevent further marginalization. Contribution: This paper highlights the importance of legal aid clinics as essential actors in the social welfare system, demonstrating their role in bridging gaps in legal access. Recommendation: The paper recommends enhancing funding and capacity for legal aid clinics, expanding their reach, and integrating them with government social welfare programs to maximize their impact.